Circadian rhythm of ischaemic core progression in human stroke. Issue 1 (26th May 2021) - Reidler, Paul; Brehm, Alex; Sporns, Peter B.; Burbano, Vanessa Granja; Stueckelschweiger, Lena; Broocks, Gabriel; Liebig, Thomas; Psychogios, Marios-Nikos; Ricke, Jens; Dimitriadis, Konstantinos; Dichgans, Martin; Kunz, Wolfgang G.; et al.
Abstract : Introduction: Experimental stroke studies suggest an influence of the time of day of stroke onset on infarct progression. Whether this holds true after human stroke is unknown, but would have implications for the design of randomised controlled trials, especially those on neuroprotection. Methods: We pooled data from 583 patients with anterior large-vessel occlusion stroke from three prospectively recruited cohorts. Ischaemic core and penumbra volumes were determined with CT perfusion using automated thresholds. Core growth was calculated as the ratio of core volume and onset-to-imaging time. To determine circadian rhythmicity, we applied multivariable linear and sinusoidal regression analysis adjusting for potential baseline confounders. Results: Patients with symptom onset at night showed larger ischaemic core volumes on admission compared with patients with onset during the day (median, 40.2 mL vs 33.8 mL), also in adjusted analyses (p=0.008). Sinusoidal analysis indicated a peak of core volumes with onset at 11pm. Core growth was faster at night compared with day onset (adjusted p=0.01), especially for shorter onset-to-imaging times. In contrast, penumbra volumes did not change across the 24-hour cycle. Discussion: These results suggest that human infarct progression varies across the 24-hour cycle with potential implications for the design and interpretation of neuroprotection trials.